101 Inspiring Stories - Xavier, G. francis (Mumbai Jaico Publishing House, 2020)
This is one of the many inspiring books from the renowned "Motivator" Dr. G. Francis Xavier. Evidently, this harvest of stories has been gleaned from lands he visited and books he read. Xavier, who conducts full-house personal growth courses has brought out this compendium in an interactive form, making the reader give the answers at the end of the story, which is a novel approach. Stories and examples are the best way to inspire and this volume can be gifted to anyone. It is useful for preachers, speakers and teachers. The book appeals to readers of all ages except the morose and irredeemable negaholics (negative thinking addicts) and anti-reading teenagers. It has stories to inspire and promises uninterrupted chuckles till the end. There are also quotations on success.
Keywords: Children Can Be Smarter